2011
DOI: 10.1016/j.neuropsychologia.2010.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Visual search patterns in semantic dementia show paradoxical facilitation of binding processes

Abstract: While patients with Alzheimer’s disease (AD) show deficits in attention, manifested by inefficient performance on visual search, new visual talents can emerge in patients with frontotemporal lobar degeneration (FTLD), suggesting that, at least in some of the patients, visual attention is spared, if not enhanced. To investigate the underlying mechanisms for visual talent in FTLD (behavioral variant FTD [bvFTD] and semantic dementia [SD]) patients, we measured performance on a visual search paradigm that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Novel or increased activities were found in all categories in the svPPA group, with the most common being an interest in puzzle activities (32%), which is in line with previous reports [18,34]. On the other hand, differences in the prevalence of artistic activities emerged between the nonfluent PPA subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Novel or increased activities were found in all categories in the svPPA group, with the most common being an interest in puzzle activities (32%), which is in line with previous reports [18,34]. On the other hand, differences in the prevalence of artistic activities emerged between the nonfluent PPA subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently an fMRI study evidenced reduction in right intraparietal sulcus activation suggesting that left-dominant laterality ratio for intraparietal sulcus may be a marker of AD progression [12]. The study of selective attention has revealed an excess of saccades, fixation and pupil dilation in visual search and feature-and-conjunction search, which is interpreted as dynamic adjustment of attentional zoom or loss of access to attentional resources, consistent with compensatory over recruitment of frontoparietal attention network [13]. An important set of literature (12.1%) was devoted to one attentional control process -inhibition.…”
Section: Eye Movements To Explore Cognition In Presumed Admentioning
confidence: 63%
“…Consistent with this interpretation, patients exhibit greater pupil dilation during difficult searches that are defined by a conjunction of target feature values, suggesting that they expend more attentional resources on searches that place greater demand on visual processing [89]. Notably, patients are able to find search targets at a comparable rate to controls, yet they still have longer response times [92]. The extended response times in patients most likely reflect slower target processing in AD, although longer motor responses may also play a minor role [90].…”
Section: Complex Viewing Behaviormentioning
confidence: 99%
“…Compared to healthy controls, patients are less accurate and have longer response times in visual search tasks [89-92]. Patients’ eye movement patterns during search have been characterized as disorganized and stochastic [31,90].…”
Section: Complex Viewing Behaviormentioning
confidence: 99%
See 1 more Smart Citation